A second look at Agathis - Bowen, M; Whitmore, T (Commenwealth Forestry Institute, University of Oxford, 1980)
Since the publication of the 'First Look at Agathis' (Whitmore, 1977) more information has come to light on many of the topics covered there; several papers have been published and seed has been collected a~d distributed as an international species/provenance trial. The Oxford-based investigation of Agathis is summarized in Bowen and Whitmore (1980), While in this paper we publish the new details not appropriated to that summary, and using the same .category headings as in Whitmore (1977). These data in conjunction with those published previously provide an up-to-date statement of knowledge of the genus. We then go on to give details of the provenance trial and a note on a pre1~inary experiment on the response of seedlings of different species to three shade conditions.